RELATIONSHIPS AMONG PROJECT MANAGER’S LEADERSHIP STYLE, TEAMWORK AND PROJECT PERFORMANCE - Akhtar Muhammad Safi; Irfan Ullah Stanikzai (International Journal of Contemporary Issues in Social Sciences, 2024)
Aim: The purpose of study is to investigate a project manager’s leadership styles and its impact on project performance and the mediating role of teamwork in the Ngo’s of Afghanistan. Methods: This study utilize direct interviews and mailed questionnaires to gather data on the impact of leadership style on project outcomes in Afghanistan, Used Structural Equation Modeling (SEM) with analysis of the results providing recommendations for future research. Results: The evaluation includes analyzing the results of the structural model, representing the relationships between variables and displaying coefficients and R-square values. Conclusion: This study confirms the positive impact of leadership style on collaboration, project performance, and stakeholder satisfaction, highlighting the importance of effective leadership in achieving successful project outcomes. Recommendation: Project Manager should focus on develop specific leadership behaviors, encourage teamwork and collaboration, and prioritize stakeholder satisfaction for improved project performance.